Mini-Review on Bioanalytical Estimation of Brinzolamide - Madrewar, Ajay B.; Deshpande, Ashwini; Bhattacharya, Sankha (Current Pharmaceutical Analysis, 2022)
Abstract: Brinzolamide is a treatment option for glaucoma. As glaucoma is the third leading cause of blindness, there is a need for analytical methods to obtain an effective drug with great precision and accuracy. Even if brinzolamide is official in IP and USP, different analytical methods still need to be brought in one place, which would help attain better results and easy comparison for other analysis specifications and procedures. This review helps to understand and gather different analysis techniques or biological fluid techniques of brinzolamide in a dosage form. These techniques include UV spectroscopy, HPLC, LC-MS, and TLC densitometry.
Keywords: UV